Isolation and Characterization of Antibacterial Compounds from Sea Urchin - Febrina Olivia Akerina; Tati Nurhayati; Ruddy Suwandi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Sea urchin is highly valued seafood. Its bioactive compound also has a potential as natural antibacterial agent. The aim of this research was to screen the antibacterial activity using cup-plate method, toxicity potential using brine shrimp lethality test (BSLT) method, bioactive compound using phytochemical method, and proximate composition by AOAC. This research was devided into two phases, the preliminary research was to determine the best body part of sea urchin showing antibacterial activity. Sea urchins were collected from Pramuka Island and extracted by meseration method. For the preliminary research, gonad extract showed the high antibacterial activity against E. coli and S. aureus at 1.83 ± 0.74 mm and 1.5 mm, respectively. The main research includes the determination of proximate composition, toxicity, bioactive compound, and antibacterial activity from the best body part of sea urchin. The proximate composition from gonad of sea urchin showed that water content 64.97 ± 0.08%; ash 2.72 ± 0.13%; lipid 19.73 ± 0.04%; protein 12.26 ± 0.3%, and 0.33 ± 0.17%, respectively. The detected bioactive compounds from the three different solvents of gonads extracts were steroid, triterpenoid and saponin. The result of lethal toxicity (LC50) from the three gonads extract was 471.861 ppm (n-hexane), 563.226 ppm (ethyl acetate) and 577.531 ppm (methanolic), respectively. Gonads ethyl acetate extracts showed the highest antibacterial activity than n-hexane and methanolic extract, its inhibition zone was 2.71 mm against S. aureus and 4.13 against E. coli. Keyword : Antibacteria, bioactive compound, D. setosum, sea urchin